FUTURE TRANSLATORS' COMMUNICATIVE COMPETENCE FORMATION BY MEANS OF PSYCHOLOGICAL TRAINING - Olha Kraievska (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
In the paper we study the problem of communicative competence of interpreters by means of psychological training techniques, taking into account the factors that impede and facilitate the work of translators. The notion of translators' professional communicative competence and the concept of secondary linguistic personality are studied. Compatibility and feasibility of psychological training techniques and exercises of various types, which are traditionally performed in the classroom by future translators at foreign language classes, are considered. The division of exercises according to the criterion of acceptance or delivery of information, that is receptive, reproductive, receptive-reproductive, productive and receptive, productive, and the communicative criterion, that is communicative, conditionally communicative and noncommunicative. The technology of  interpreters' communicative competence formation is revealed.